Glory days - King, Tony (Macmillan Education OxfordGB, 2004)
Presents profiles of 25 outstanding West Indian cricketers spread over 5 epochs beginning with the early years 1929-1939; through the post-war years; the Worrel-Sobers era; world supremacy 1975-1995; and the present. Each profile features career statistics and highlights, supported by superbly chosen game-in-action photographs. Explores the unique significance of cricket to West Indians; the 'glory story' of the team; and discusses factors necessary for reclaiming world dominance.